Maarif: transformation of a concept in the Ottoman Empire at the beginning of the nineteenth century - Yildiz, Aytac; Gunduz, Mustafa (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2019)
During the Ottoman period, 'science (ilim, pl. ulum)', 'knowledge (marifet, pl. maarif)' and 'technique (fen, pl. funun)' emerged as three important concepts of knowledge. Maarif, which came into prominence with Selim III, began to undergo a semantic transformation together with the concepts of ulum and funun and by the time of Mahmud II it had become an overarching concept representing the knowledge dimension of the new era. This article discusses the semantic transformation of maarif, focusing on the period between 1789 and 1839. This study applies the history of concepts approach developed by Reinhart Koselleck, whereby a synchronic analysis of the concept of maarif is undertaken alongside an examination of its diachronic dimension. This reveals an ambiguous and multi-dimensional structure and helps us to account for its evolution as an umbrella term.
Keywords: Knowledge; science; history of concepts; Ottoman education; Ottoman modernisation; Education & Educational Research; Social Sciences - Other Topics